A Case of Pulmonary Hamartoma Showing Rapid Growth - Masamichi Itoga; Yoshiki Kobayashi; Masahide Takeda; Yuki Moritoki; Mami Tamaki; Kenji Nakazawa; Toru Sasaki; Hayato Konno; Ikuo Matsuzaki; Shigeharu Ueki (Case Reports in Medicine)
A 65-year-old man was admitted for detailed examination of a growing nodular shadow in the left lung. The nodular shadow was initially detected in a routine chest X-ray check-up in March 2012 that warranted regular chest X-ray follow-up. The nodular shadow increased in size from 12 × 15 mm to 15 × 20 mm within five months. The calculated tumor doubling time (TDT) in our case was approximately 132.2 days. A malignant tumor was strongly suspected based on the rapid growth, and tumorectomy was thus performed. Cartilaginous tissue accounted for most of the pathological specimen, but a small amount of an epithelial component was observed histologically, and we diagnosed a hamartoma. Hamartoma generally shows slow annual growth, but it is important to recognize that rapid enlargement occurs in some cases.